MODEL KONSEPTUAL PERKEMBANGAN DELTA SEPINGGAN, INTERVAL âMFS 1-MFS 5â, BLOK SOUTH MAHAKAM, CEKUNGAN KUTAI, KALIMANTAN TIMUR - Permana, Irfandi Oky; Nugroho, Hadi; Hidajat, Wahju Krisna (Geological Engineering E-Journal, 2014)
The energy demandÂ  are growing by day,Â  especially in Indonesia, whereas these needs are not matched by the number of oil and gas production in Indonesia. This case is evidenced by the release of Indonesia as a member of an organization of oil exporting countries on October 9-10, 2008 in Vienna (Kompas, 10 October 2008). Thus required a study on the potential of producing hydrocarbon basin that will be expected to meet the energy demand of the oil and gas in Indonesia. One of the basins in Indonesia is the Kutai Basin which is the largest and widest Tertiary Basin in western Indonesia. The study area is located at the South Mahakam, Kutai Basin, East Kalimantan. This study aims to make conceptual model of delta Sepinggan development. The method included analysis of well log analysis method, 2D seismic analysis method, method of data analysis of rock core and biostratigraphic data analysis method. Based on analysis results can be obtained in the form of variations in lithology information on Sepinggan Zone deltaic sequence at intervals of MFS 1-MFS 5 marker are coal, sandstone, shale and limestone. Â Process on Sepinggan Delta are regretion process dominated on Early Miocene â Middle Miocene (N4-N14), and transgretion process on Middle Miocene âLate Miocene (N14-N16). Sedimentation process influenced by East Manpatu Fault that increasing accomodation space in Rocky Field area, so sediment layer in Rocky Field area is thicker 60-150 meter than Zahra-Zidane Field area.